The mediating effect of innovation on the relationship between TQM and organizational performance in Saudi public higher education colleges - Alzahrani, Murshid Mohammed (2017)
The purpose of this study was to investigate the relationship between total quality management (TQM); innovation (INV) and organizational performance (OP) in i higher education institutions (HEis) in Saudi. The TQM core elements included leadership commitment, strategic planning, continuous improvement, customer focus, process focus, employee involvement, training and learning, rewards and recognition, and management by fact. Innovation included product innovation and process innovation, meanwhile, measures of organizational performance included student-related academic achievement and non-student related academic achievement. Based on the theoretical framework, the main hypotheses were developed, and statistically tested. The study used the cross-sectional survey methodology. The samples were drawn from the Saudi HEls (public universities) using the random sampling procedure based on the directory provided by the Ministry of Higher Education in Saudi. The final number of respondents involved in this study was 250 colleges (faculties) in 24 public universities. The hypotheses of the study were tested by applying the multivariate statistical data analyses. This study reported significant relationships between TQM core elements and innovation, between TQM core elements and OP measures, and between innovation and OP measures. In brief, the results supported all the main hypotheses and provided evidence that both the TQM core elements and innovation should be implemented holistically, rather than piecemeal. In addition, the study found that innovation fully mediates the relationship between TQM and OP. The current study provides insight into the relationship between TQM, INV and OP. Hence, this study is able to expand the boundary of the existing literature. Finally, the findings of this study provide empirical evidence that TQM has a significant and positive impact on innovation, which in tum, significantly affects organizational performance.